Design of Electronic PID Controller Using Genetic Algorithms (مجلة المنصور, 2022)
This paper presents a Genetic Algorithm (GA)- based electronic Proportional-Integral-Derivative (PID)Controller tuner. The tuning is based upon the maximization of a comprehensive fitness functionconstructed as the inverse of Peak Overshoot (Mp). This approach has a some advantages, it gives a clearer andsimpler representation of the problem, simplifies chromosome construction, and totally avoids using binaryencoding and decoding so as to simplify software programming. This paper addresses to demonstrate the capabilityof GA's to solve complex and constraint optimization Problems via utilizing GA's as a general-purposeoptimizing tool to solve different Control system design problems.